Gambaran Stres Pada Mahasiswa Yang Menyukai Musik Akustik - Gani, Muhammad Rizani; Mulyani, Mulyani; Fadhila, Mahdia (Islamic Psychology Study Program, Faculty of Ushluddin and Humanities, UIN Antasari Banj, 2022)
Pressure during learning and all conflicts can hurt the psychology of students themselves, one of which is stress. The difficulties of adolescents and students in dealing with stress need to be balanced with practical and inexpensive coping strategies because if stress is left alone, it can threaten the individual's health. Preliminary studies show that acoustic music can be a practical and inexpensive solution to overcome stress experienced by students as a form of emotion-centered coping because the character of the music is slow soft and can focus listeners on channeling expressions through lyrics that represent individual emotions and feelings. This study aims to determine the description of stress in students who like acoustic music and to find out how the role of acoustic music on student stress. This research is a qualitative descriptive study with ten subjects with specific criteria. The data collection methods used were interviews, observation, the perceived stress scale (PSS-10), and the documentation method. The results of this study indicate that the ten subjects have different stressors, symptoms, and stress levels; each subject also uses acoustic music as emotional coping that helps the emergence of positive reactions such as feeling calmer, more focused, and channeled—subject's feelings.